2021
DOI: 10.1002/jcp.30269
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin maintains inner blood‐retinal barrier via inhibition of p38/TXNIP/NF‐κB pathway in diabetic retinopathy

Abstract: The pathophysiology of diabetic retinopathy (DR) was complex. Under hyperglycemic conditions, the release of proinflammatory cytokines and the adhesion of leukocytes to retinal capillaries contribute to endothelial damage and the subsequent increase in vascular permeability resulting in macular edema. Melatonin, produced in the retina to regulate redox reactions and dopamine metabolism, plays protective roles against inflammation and oxidative stress. Considering its anti‐inflammatory and antioxidative propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
5
28
0
Order By: Relevance
“…The DM model resulted in the development of hyperglycemia, reduction of a and b waves and oscillatory potential amplitude of electroretinography (ERG), and an increase in GFAP and vascular endothelial growth factor (VEGF) levels. Data from previous studies corroborate the alterations in a and b waves of the ERG by DM [ 52 , 53 ]. MEL did not affect glucose metabolism, but did prevent a decrease in the a wave, b wave [ 51 , 53 ] and the amplitude of the oscillatory potential of the ERG of diabetic rats.…”
Section: Diabetic Neuropathy and Retinopathysupporting
confidence: 85%
See 2 more Smart Citations
“…The DM model resulted in the development of hyperglycemia, reduction of a and b waves and oscillatory potential amplitude of electroretinography (ERG), and an increase in GFAP and vascular endothelial growth factor (VEGF) levels. Data from previous studies corroborate the alterations in a and b waves of the ERG by DM [ 52 , 53 ]. MEL did not affect glucose metabolism, but did prevent a decrease in the a wave, b wave [ 51 , 53 ] and the amplitude of the oscillatory potential of the ERG of diabetic rats.…”
Section: Diabetic Neuropathy and Retinopathysupporting
confidence: 85%
“…Data from previous studies corroborate the alterations in a and b waves of the ERG by DM [ 52 , 53 ]. MEL did not affect glucose metabolism, but did prevent a decrease in the a wave, b wave [ 51 , 53 ] and the amplitude of the oscillatory potential of the ERG of diabetic rats. In addition, MEL prevented the increase in GFAP levels in Müller cells and VEGF in the retina.…”
Section: Diabetic Neuropathy and Retinopathysupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have also reported that TXNIP was highly expressed in diabetic complications (Xu et al, 2013;Lv et al, 2020). For example, the inhibition of the p38/TXNIP/NF-κB pathway by melatonin is suggested to maintain the inner blood-retinal barrier in DR (Tang et al, 2021). Moreover, TXNIP overexpression has been demonstrated to activate autophagy and apoptosis in the rat müller cells treated with high glucose in DR (Ao et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…At 2 h after STZ injection, the right eye of rats was intravitreally injected with melatonin (30 μg/eye, 2 μl; Sigma-Aldrich), while the left eye was injected with the equivalent volume of normal saline. Intravitreal injection of melatonin was repeated every week based on our previous study ( 18 ), and the rats were killed at 8 weeks after diabetes onset. The rats that failed to develop diabetes and with intraocular damages (e.g., traumatic cataract, intraocular hemorrhage, inflammation) were excluded from the experiments.…”
Section: Methodsmentioning
confidence: 99%